HYDROGEOPHYSICAL INVESTIGATION OF GROUNDWATER POTENTIAL, LITHOLOGICAL STRATA AND AQUIFER VULNERABILITY IN PARTS OF DELTA NORTH DISTRICT, NIGERIA - Chinyem, Felix Iwebunor; Abriku, Ezekiel Onoriode; Ovwamuedo, Glory; Salami, Sikiru Adeoye; Igili, Chinedu Ojo; Nwugha, Victor Ndubuisi; Osieke, Jeffrey Onyedikachi (FUDMA Journal of Sciences, 2026)
Groundwater in Delta North District of Nigeria, constitutes the main source of potable water to inhabitants, however increasing demographics, urbanization and poor water disposal practices have raised serious concerns about aquifer vulnerability, as well as declining water quality. The goal of this study is to investigate the groundwater potential, lithological strata and aquifer vulnerability, in parts of the district, using vertical electrical sounding (VES) technique. Twenty-five (25) VES, using Schlumberger array was employed to delineate subsurface geoelectric layers as well as infer the aquiferous units, while eight (8) boreholes were drilled to assess the lithology and aquifer properties of the study area. Geoelectric models interpreted, were correlated with the obtained well logs in order to validate the lithological strata and aquifer depths. Result revealed a heterogeneous subsurface geologic formation, comprising, top soil, clayey sand, lateritic clayey sand, coarse sand, medium-coarse sand, fine-medium sand and saturated deep sandy aquifers occurring at varying depths ranging from 66 m to 152 m and beyond. The result of aquifer resistivity, depth, transmissivity and transverse resistivity indicate moderate to good groundwater prospects. Aquifer vulnerability assessment indicates that the aquifers are moderately to highly vulnerable to surface contamination. Thus, this study has provided a reliable insight into groundwater availability and vulnerability in the study area as well as recommend an adequate development of deeper aquifers and proper waste management measures for sustainable groundwater development.
Keywords: Sustainable groundwater development, aquifer vulnerability, groundwater potential, Delta North District